Identification and tissue-specific characterization of novel SHOX-regulated genes in zebrafish highlights SOX family members among other genes - Hoffmann, Sandra; Röth, Ralph; Hassel, David; Rappold, Gudrun (Frontiers in genetics, 2021)
SHOX deficiency causes a spectrum of clinical phenotypes related to skeletal dysplasia and short stature, including Léri-Weill dyschondrosteosis, Langer mesomelic dysplasia, Turner syndrome, and idiopathic short stature. SHOX controls chondrocyte proliferation and differentiation, bone maturation, cellular growth arrest and apoptosis via transcriptional regulation of its direct target genes NPPB, FGFR3, and CTGF. However, our understanding of SHOX-related pathways is still incomplete. To elucidate the underlying molecular mechanisms and to better understand the broad phenotypic spectrum of SHOX deficiency, we aimed to identify novel SHOX targets. We analyzed differentially expressed genes in SHOX-overexpressing human fibroblasts (NHDF), and confirmed the known SHOX target genes NPPB and FGFR among the most strongly regulated genes, together with 143 novel candidates. Altogether, 23 genes were selected for further validation, first by whole-body characterization in developing shox-deficient zebrafish embryos, followed by tissue-specific expression analysis in three shox-expressing zebrafish tissues: head (including brain, pharyngeal arches, eye, olfactory epithelium), heart, and pectoral fins. Most genes were physiologically relevant in the pectoral fins, while only few genes were also significantly regulated in head and heart tissue. Interestingly, multiple sox family members (sox5, sox6, sox8, sox18) were significantly dysregulated in shox-deficient pectoral fins together with other genes (nppa, nppc, cdkn1a, cdkn1ca, cyp26b1, cy26c1), highlighting an important role for these genes in shox-related growth disorders. Network-based analysis integrating data from the Ingenuity pathways revealed that most of these genes act in a common network. Our results provide novel insights into the genetic pathways and molecular events leading to the clinical manifestation of SHOX deficiency.